Textured Foot Orthotics on Dynamic Stability and Turning Performance in Parkinson's Disease. Issue 4 (3rd July 2020) - Robb, Kelly A.; Perry, Stephen D.
Abstract: The purpose of this study was to facilitate sensory feedback, with textured foot orthotics, to evaluate dynamic stability and turning behavior in Parkinson's disease individuals. Seven participants with a diagnosis of idiopathic Parkinson's disease, aged 55–80 years old, participated in this study. Participants completed three testing sessions; baseline, 4 weeks post-baseline, and 5 weeks post-baseline. Three experimental conditions were tested: footwear only (F), footwear + non-textured orthotic (FO), and footwear + textured orthotic (FOT). Kinematic, kinetic, and video data were collected during the steps preceding a turn task. Variables of interest included dynamic stability (maximum mediolateral (ML), minimum ML, and ML range of the center of mass (COM)-base of support (BOS) relationship) and turning performance (gait velocity and step count). There was a statistically significant increase in maximum ML COM-BOS distance (week 4 [0.1298 m ± 0.054] compared to week 0 [0.1069 m ± 0.050] p = .0076), and a significant decrease in step count (week 0-F [5.52 steps ± 1.08] to week 0-FO [5.23 steps ± 0.87] p = .0296) and (week 4-FO [5.24 steps ± 1.31] to week 4–FOT [4.67 steps ± 0.76] p = .0004). Textured foot orthotics modified dynamic stability and turning performance in Parkinson's disease individuals completing a 180° degree turn. These preliminary results support this potential treatment option for rehabilitation professionals treating Parkinson's disease.